Influence of crosslinks and entanglements on hydrogel reinforcement: insights from molecular dynamics simulations - Zhu, Panpan; Fu, Yimou (Frontiers in Materials, 2025)
Entanglements and crosslinking jointly govern the mechanical performance of polyacrylamide (PAAm) hydrogels, yet their molecular roles remain poorly quantified. This study uses dissipative particle dynamics simulations to disentangle crosslinker concentration, inter-chain and intra-chain entanglement contributions to hydrogel stiffness and hardening effect. Systems were built at a uniform acrylamide (AAm) monomer concentration and identical chain length, with the crosslinker concentration varied to assess its impact. Separately, entanglement degree was modulated by varying chain length distributions under fixed crosslinking, and water content was adjusted to tune inter-chain entanglement density at constant intra-chain entanglement and crosslinker loading. Uniaxial tensile tests characterized stress-stretch responses. Our results reveal that increasing crosslinker density marginally elevates hardening effect but plateaus at higher concentrations, whereas higher inter-chain entanglement produces pronounced hardening and network resilience. Under constant crosslinking, systems with elevated entanglement exhibit significantly hardening and maintain structural integrity during large deformations. Moreover, reducing water content increases monomer concentration and inter-chain entanglements, thereby amplifying stiffness without altering intra-chain entanglement trends. These findings demonstrate that inter-chain entanglements act as dynamic “physical crosslinks,” enabling efficient load transfer and preventing network relaxation. Our study provides atomistic insight into the reinforcement mechanisms of hydrogels and offers design guidelines for tougher soft materials.